2021
DOI: 10.1029/2021jd035479
|View full text |Cite
|
Sign up to set email alerts
|

Observations and Modeling of Rime Splintering in Southern Ocean Cumuli

Abstract: Recent studies have suggested a correct representation of cloud phase in the Southern Ocean region is important in climate models for an accurate representation of the energy balance. Satellite retrievals indicate many of the clouds are predominantly liquid, despite their low temperatures. However, clouds containing high numbers of ice crystals have sometimes been observed in this region and implicated the secondary ice production process called rime splintering. This study re‐examines rime splintering in Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Further, the PID scheme suggests ice growth occurs with decreasing altitude in convective clouds, with P[large ice] ∼10% 150 m below cloud top and P[large ice] ∼50% 700 m below cloud top. This is consistent with previous studies that have shown higher updraft velocities provide a preferential environment for the growth of ice in supersaturated regimes (McFarquhar et al., 2011; Rosenow et al., 2014; Wang et al., 2020), and that SIP during SOCRATES was enhanced in convective regions exhibiting multiple updrafts (including embedded convective elements within stratocumulus clouds), with thin stratiform clouds with a lack of significant updraft activity exhibiting little SIP and remaining mostly composed of SLW (Järvinen et al., 2022; Lasher‐Trapp et al., 2021; Mace et al., 2021). The peak P[any ice] for any part of the cloud averaged among both methods is ∼65% for convective clouds and ∼20% for stratiform clouds, suggesting that ice is about 3 times more likely in convective clouds than in stratiform clouds.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the PID scheme suggests ice growth occurs with decreasing altitude in convective clouds, with P[large ice] ∼10% 150 m below cloud top and P[large ice] ∼50% 700 m below cloud top. This is consistent with previous studies that have shown higher updraft velocities provide a preferential environment for the growth of ice in supersaturated regimes (McFarquhar et al., 2011; Rosenow et al., 2014; Wang et al., 2020), and that SIP during SOCRATES was enhanced in convective regions exhibiting multiple updrafts (including embedded convective elements within stratocumulus clouds), with thin stratiform clouds with a lack of significant updraft activity exhibiting little SIP and remaining mostly composed of SLW (Järvinen et al., 2022; Lasher‐Trapp et al., 2021; Mace et al., 2021). The peak P[any ice] for any part of the cloud averaged among both methods is ∼65% for convective clouds and ∼20% for stratiform clouds, suggesting that ice is about 3 times more likely in convective clouds than in stratiform clouds.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor potentially enhancing production of ice in the stratocumulus clouds is related to the multi‐cell structure of the clouds (see Section 5.1) (Lasher‐Trapp et al., 2021; Mossop et al., 1970). Ice crystals from older cells can be incorporated into newly forming rising cells, where they can initiate ice multiplication processes.…”
Section: Possible Sip Mechanisms In So Stratocumulus Cloudsmentioning
confidence: 99%
“…The minimum temperatures during the segments varied between −0.5 and −9.3°C. For a more detailed discussion of cumulus systems in SOCRATES we refer to Lasher-Trapp et al (2021).…”
Section: Cloud Types Analyzedmentioning
confidence: 99%
See 1 more Smart Citation
“…Using measurements from SOCRATES in combination with high‐resolution numerical modeling, Lasher‐Trapp et al. (2021) re‐examined SIP in the Southern Ocean cumuli, and found that the measured Ni exhibits 7 orders of magnitude or more higher than INP number concentrations, which is also reproduced by their numerical modeling. Based on the global cloud‐resolving simulations, Atlas et al.…”
Section: Introductionmentioning
confidence: 96%